Inclusión de harina de ají como coccidiostato en dos densidades poblacionales y su influencia en parámetros productivos en pollos COBB 500 - Morales Morales, Kleber Fernando (2016)
This research evaluated the inclusion of three levels pepper flour as coccidiostat two population densities on behavior in broilers Cobb 500. treatment T0A and T0B (350g salinomycin / ton of food with 8and 10 chickens / m2), T1A and T1B (500g flour pepper / ton of food with 8and 10 chickens / m2), T2A and T2B (: Eight treatments were used pepper flour 500g / ton of food with 8and 10 chickens / m2) and T3A and T3B (pepper 1000g flour / ton of food with 8and 10 chickens / m2). Cobb 288 birds of 500 line, distributed in eight treatments and four replications were used. The data were evaluated using a two-factor design completely at random, using the Tukey test at 0,05. The study variables were: feed intake, weight, feed conversion efficiency Index Europe (IEE), processed through the statistical package InfoStat 2016. In the final registration: final weight obtained 2411,67g treatment T2B (± 148, 99) being numerically superior to others would find treatment without significant difference (p> 0,05); the higher feed intake corresponds to T1A with 4524,18g (± 514) to be significant (p <0,05); T0B feed conversion was more efficient with 1,69 (± 0,3), being highly significant (p <0,01); European efficiency index obtained T2A (319,91) than the other treatments. With the results established that a dose of 500g / ton of flour aji better yields in weight gain, carcass yield, better profitability also reduced the amount of Eimeria oocysts.